Psychosocial influences on pain in transgender individuals - Clemens, Kelly S.; Matkovic, John; Odelson, Abby; Strain, Audrey; Wesselmann, Eric D. (Frontiers in Pain Research, 2025)
Pain is an unpleasant and unavoidable part of the human experience, but the prevalence and impact of pain disproportionately impacts marginalized groups, including transgender and gender-diverse people. While there are many bases of pain, psychosocial variables, including cognitions (e.g., outcome and interpersonal expectations, social gender norms), affect (e.g., negative affectivity, emotional distress), and social factors (e.g., social exclusion) may be particularly relevant in the pain experiences of transgender individuals. The coalescence of these factors is discussed in this review, where authors specifically consider how these cognitive, affective, and social factors may contribute to pain disparities seen in transgender individuals. Patient-centered communication is presented as a potential avenue to directly mitigate the effect of these psychosocial variables on pain in transgender individuals by reducing feelings of social exclusion transgender patients may experience in the medical office, and the authors call for additional experimental research and the development of educational interventions for providers.